Shear and Elongational Flow Properties of Long-Chain Branched Poly(ethylene terephthalates) and Correlations to Their Molecular Structure - Härth, Michael; Kaschta, Joachim; Schubert, Dirk W. (Macromolecules, 2014)
Reactive processing with low-molar-mass modifiers is a well-known method to create long-chain branched (LCB) structures in a poly(ethylene terephthalate) (PET) melt. However, less is known about the elongational flow properties of LCB-PET. Therefore, the aim of this contribution is (a) to generate LCB molecules and (b) to evaluate the influence of the branching level on the transient elongational behavior. For this purpose, a commercial, linear PET and different contents (0.1-0.3 wt %) of the tetrafunctional modifier pyromellitic dianhydride (PMDA) were reactively processed. All samples were analyzed by size exclusion chromatography coupled with a light scattering device and characterized by shear and elongational rheometry. It was found that the molar mass distribution of the modified materials exhibit a high molar mass shoulder, leading to an increase of the weight-average molar mass and a broadening of the molar mass distribution. Moreover, the Mark-Houwink plot of the modified materials displays deviations from the power law toward lower intrinsic viscosities, which indicate the existence of LCB molecules. The shear viscosity shows a pronounced shear thinning behavior and a remarkable increase at low frequencies compared to the linear PET. Considering the transient elongational viscosity, a distinguished strain hardening is observed, which increases with increasing PMDA content and with increasing strain rate. From the results of the rheological and molecular characterization and by considering the chemical reaction mechanisms, it can be concluded that the PET modified with high PMDA contents has a treelike branch-on-branch architecture, which is well-known from low-density polyethylene melts.